Rapid and low‐temperature synthesis of MoAlB MAB phase by using stress‐induced Al‐particles - Maharshi Dey; Quan Tran; Jin Zhang; Godswill Ngige; Sabah Javaid; Michelle Pantoya; Surojit Gupta (International Journal of Ceramic Engineering & Science)
Abstract Currently, MoAlB particles are produced at 1000°C and higher temperatures. In this manuscript, we report the rapid synthesis of MoAlB by altering the stress of Al particles to affect Al reactivity. The Al particles were purposefully stress‐altered to reduce their threshold for reaction. The stress‐altering process consisted of annealing followed by quenching of the aluminum powder. The combined process caused a reaction at a lower temperature between Mo, B, and Al to form MoAlB. The stress‐altering of Al particles (i.e., Al [TT‐treated]) was effective in producing >95 wt.% MoAlB after reaction at only 700°C for 10 min, a significant reduction in temperature. Based on these results, we can further project that this process can be used for manufacturing Al‐based compositions at significantly lower temperatures.